In Vivo Genome Editing Restores Dystrophin Expression and Cardiac Function in Dystrophic Mice - Mona El Refaey; Li Xu; Yandi Gao; Benjamin D. Canan; T. M. Ayodele Adesanya; Sarah C. Warner; Keiko Akagi; David E. Symer; Peter J. Mohler; Jianjie Ma; Paul M.L. Janssen; Renzhi Han (2017)
Rationale: Duchenne muscular dystrophy is a severe inherited form of muscular dystrophy caused by mutations in the reading frame of the dystrophin gene disrupting its protein expression. Dystrophic cardiomyopathy is a leading cause of death in Duchenne muscular dystrophy patients, and currently no effective treatment exists to halt its progression. Recent advancement in genome editing technologies offers a promising therapeutic approach in restoring dystrophin protein expression. However, the impact of this approach on Duchenne muscular dystrophy cardiac function has yet to be evaluated. Therefore, we assessed the therapeutic efficacy of CRISPR (clustered regularly interspaced short palindromic repeats)-mediated genome editing on dystrophin expression and cardiac function in mdx/Utr +/− mice after a single systemic delivery of recombinant adeno-associated virus. Objective: To examine the efficiency and physiological impact of CRISPR-mediated genome editing on cardiac dystrophin expression and function in dystrophic mice. Methods and Results: Here, we packaged SaCas9 (clustered regularly interspaced short palindromic repeat–associated 9 from Staphylococcus aureus ) and guide RNA constructs into an adeno-associated virus vector and systemically delivered them to mdx/Utr +/− neonates. We showed that CRIPSR-mediated genome editing efficiently excised the mutant exon 23 in dystrophic mice, and immunofluorescence data supported the restoration of dystrophin protein expression in dystrophic cardiac muscles to a level approaching 40%. Moreover, there was a noted restoration in the architecture of cardiac muscle fibers and a reduction in the extent of fibrosis in dystrophin-deficient hearts. The contractility of cardiac papillary muscles was also restored in CRISPR-edited cardiac muscles compared with untreated controls. Furthermore, our targeted deep sequencing results confirmed that our adeno-associated virus-CRISPR/Cas9 strategy was very efficient in deleting the ≈23 kb of intervening genomic sequences. Conclusions: This study provides evidence for using CRISPR-based genome editing as a potential therapeutic approach for restoring dystrophic cardiomyopathy structurally and functionally.